2013
DOI: 10.1111/pme.12231
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in Sleep Quality and Duration Is Related to Cerebral Mu Opioid Receptor Binding Potential during Tonic Laboratory Pain in Healthy Subjects

Abstract: Objective Although poor sleep is a consequence of pain, sleep disturbance reciprocally induces hyperalgesia and exacerbates clinical pain. Conceptual models of chronic pain implicate dysfunctional supraspinal pain processing mechanisms, mediated in part by endogenous opioid peptides. Our preliminary work indicates that sleep disruption impairs psychophysical measures of descending pain modulation, but few studies have investigated whether insufficient sleep may be associated with alterations in endogenous opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Several reports have found a relationship between catastrophizing and temporal summation of pain, a marker of CS(17;18). A number of published reports have documented the relationship between poor/disturbed sleep and hyperalgesia(7;20). In addition, one study by members of our group found that a significant proportion of variance in clinical pain severity and pain-related interference attributable to pain catastrophizing was actually mediated by sleep disturbance in a facial pain population(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have found a relationship between catastrophizing and temporal summation of pain, a marker of CS(17;18). A number of published reports have documented the relationship between poor/disturbed sleep and hyperalgesia(7;20). In addition, one study by members of our group found that a significant proportion of variance in clinical pain severity and pain-related interference attributable to pain catastrophizing was actually mediated by sleep disturbance in a facial pain population(16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the primary aims, we also explored the extent to which pain catastrophizing moderated the association of subjective sleep efficiency, which has well-documented associations with clinical and laboratory pain(20) as well as catastrophic thinking(14;21), and CS across subjects. The diary measure of sleep efficiency was chosen as it is widely used and well-validated in older adults(22) and represents individual’s perception of their own sleep.…”
mentioning
confidence: 99%
“…on SES, such as chronic pain 64 and psychological illness, 65 may also interfere with attempts to obtain adequate sleep. Detailed research that collects individual level, real-time data on noise exposure, activity levels, stress hormones, and sleep length and quality are needed to better define the opportunities for intervention to improve sleep health in those living in deprived areas.…”
Section: Discussionmentioning
confidence: 99%
“…These and other pre-clinical studies have found that sleep loss alters molecular pathways in cerebral MOR activated anti-nociceptive circuits in the periaqueductal grey, hypothalamus, and mesolimbic structures, providing a neurobiological substrate supporting the current findings. In addition, a prior [ 11 C] Carfentanil Positron Emission Tomography (PET) study provides correlational support in humans, demonstrating that short sleep duration was associated with increased MOR availabilty during experimental pain (indicating down regulation of cerebral MOR or diminished release of endogenous opioid peptides) in brain structures associated with pain inhibiton (i.e., anterior cingulate gyrus and dorsolateral preforntal cortex) 31 .…”
Section: Discussionmentioning
confidence: 95%